Toll-like receptor (TLR) 2 and TLR4 differentially regulate doxorubicin induced cardiomyopathy in mice. - Yonggang Ma (Public Library of Science (PLoS), 2012)
Recent evidence indicates that toll-like receptor (TLR) 2 and 4 are involved in the pathogenesis of dilated cardiomyopathy (DCM), but the exact mechanisms of their actions have not been elucidated. We explored the therapeutic potential of blocking TLRs in mice with established cardiomyopathy. Cardiomyopathy was generated by a single intraperitoneal injection of doxorubicin (10 mg/kg). Two weeks later, the mice were treated with TLR2 or TLR4 neutralizing antibody. Blocking TLR2, but not TLR4, activity not only reduced mortality, but also attenuated doxorubicin-induced cardiac dysfunction by 20% and inhibited myocardial fibrosis. To determine the differential effects of blocking TLR2 and TLR4 in chronic cardiomyopathy, mice were injected with doxorubicin (3.5 mg/kg) once a week for 8 weeks, followed by treatment with TLR2 or TLR4 neutralizing antibody for 40 days. Blocking TLR2 activity blunted cardiac dysfunction by 13% and inhibited cardiac fibrosis, which was associated with a significant suppression of myocardial inflammation. The underlying mechanism involved interrupting the interaction of TLR2 with its endogenous ligands, resulting in attenuation of inflammation and fibrosis. In contrast, blocking TLR4 exacerbated cardiac dysfunction and fibrosis by amplifying inflammation and suppressing autophagy. Our studies demonstrate that TLR2 and TLR4 play distinct roles in the progression of doxorubicin-induced DCM. TLR4 activity is crucial for the resolution of inflammation and cardiac fibrosis, while blocking TLR2 activity has therapeutic potential for the treatment of DCM.